Perception about Intrauterine Devices, Prior to and After Placement-Prospective Survey - Andreia de Vasconcelos Gaspar; Isabel Santos Silva; Maria do Céu Almeida (IMR Press, 2022)
Background: Intrauterine devices are effective long-lasting contraceptive methods with a high rate of satisfaction among users. This study aimed at determining women's perception of intrauterine contraception, before and after its placement, and assessing the impact of contraceptive counseling on that perception. Methods: Descriptive prospective study, carried out through a questionnaire, regarding women who underwent a Family Planning (FP) consultation in a Tertiary Hospital Center, from September 1, 2020 to August 31, 2021. Results: 108 women were included in this study. Contraceptive methods used prior to the consultation were mainly hormonal (62%) and barrier (30%). The main reason for choosing the intrauterine device was the advice given by the physician or other health professional (87%). The greatest concern of women regarding this method was the placement process (27%), especially with regard to pain associated with the procedure (50%). 79% of women considered that they were fully clarified prior to device placement. After placement, mean pain intensity was 3.94 (SD = 2.273; Visual Analogue Scale), and it was found to be lower than women's perception prior to placement. 73% thought the process was simpler than expected and 88% would advise the method to other women. All users reported having been informed about possible complications or adverse effects associated with this contraceptive method. Conclusions: Results indicate that the choice of long-acting contraception is mainly associated with correct medical advice. Most of the women were clear after family planning consultation, which made the intrauterine device placement easier and less painful than expected.